Fecal excretion of bile acids: a new technique for studying bile acid kinetics in patients with ileal resection - Woodbury, James F. (1971)
The fecal elimination and enterohepatic circulation of bile acid was studied in 11 patients. 10 patients with varying degrees of ileal disease or resection and 1 patient with pancreatic insufficiency and no ileal disease. A new technique was employed which involved the nearly simultaneous administration of cholic acid-(14)C and a nonabsorbable marker. (51)CrCl(3). Each individual stool specimen was collected for 36-96 hr and analyzed separately. Assay of the radioactivity of each isotope allowed the accurate determination of an excretion rate for both cholic acid and (51)Cr. The difference between these rates was used to calculate an absorption coefficient for cholic acid. In addition, bile acid concentration measured by the steroid dehydrogenase technique, and the water content of each stool was determined. The patients were divided into groups depending upon how much small intestine was resected or diseased: six patients with less than 100 cm of ileal resection or disease (group A), and five patients with more than 100 cm of ileal disease or resection (group B). The (51)Cr excretion rate was similar in the two groups, but cholic acid-(24)C excretion rates were significantly more rapid in group B than in group A. The cholic acid absorption coefficient was essentially normal in the patient with pancreatic insufficiency, moderately decreased in group A patients, and extremely low or zero in group B patients. It was inversely related to the length of intestine diseased or resected. Daily fecal bile acid excretion was normal to twice normal in group A patients and 2-8 times normal in group B patients. In all patients with ileal disease or resection, there was a direct correlation between fecal bile acid, fecal mass, and fecal water. Each millimole of additional bile acid in the stool was associated with an increase in stool water of 11 moles (P < 0.01). These studies show that the kinetics of bile acids in the enterohepatic circulation can be accurately studied in patients with extensive ileal resection. The regular relationship between fecal bile acid and fecal mass and water suggests, but does not prove, a critical role of bile acid in determining stool water.